Pengaruh Variabel Sosial Demografi dan Sosial Ekonomi Terhadap Partisipasi Kerja Penduduk Lanjut Usia - Kartika, Ni Putu Rusmala Dewi; Sudibia, I Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2014)
Economic progress , environmental improvement , and the advancement of science, mainly due to the advances of medical science , can increase life expectancy (life expectancy ) . Fieldwork aims to analyze the influence of socio-demographic variables and socioeconomic work against participation of the elderly population . This research was conducted in the village of Penatih the number of samples taken is as much as 87 samples with simple random sampling method . Data collected through questionnaires . The analysis technique used is multiple linear regression analysis techniques . Based on the results of the analysis found that socio-demographic variables which include the elderly marital status , education, the elderly , and elderly health and socioeconomic variables include household income elderly and elderly dependency simultaneously affect the labor participation of the elderly population . Elderly marital status , education, elderly , elderly health , household income elderly partially negative effect on the labor force participation of the elderly . Elderly dependency simultaneous positive effect on the labor participation of the elderly population . The most dominant variable is the variable health of the elderly.
Keywords: elderly; socio-demographic; socio-economic; labor participation of the elderly